Modeling, simulation and control of a doubly-fed induction generator for wind energy conversion systems - Boumerid Bensahila Med El Amine; Allali Ahmed; Merabet Boulouiha Houari; Denai Mouloud (Institute of Advanced Engineering and Science, 2020)
In recent years, wind energy has become one of the most promising renewable energy sources. Various wind turbine concepts with different generator topologies have been developed to convert this abundant energy into electric power. The doubly-fed induction generator (DFIG) is currently the most common type of generator used in wind farms. Usually the DFIG generator is a wound rotor induction machine, where the stator circuit is directly connected to grid while the rotor’s winding is connected to the grid via a three-phase converter. This paper describes an approach for the independent control of the active and reactive powers of the variable-speed DFIG. The simulation model including a 1.5 MW-DFIG driven by a wind turbine, a PWM back-to-back inverter and the proposed control strategy are developed and implemented using MATLAB/Simulink/SimPowerSystems environment.